'Feet in Both Places': Affective Spaces of Circular Migration. (November 2019) - Shivanand, Swathi
This article studies the experience of being a circular migrant, of having 'feet in two places'. It focusses on residents of two migrant settlements in Bengaluru who are originally from the Hyderabad–Karnataka region and work as construction labourers in the city. Through interviews with these migrant-residents, I explore the affective and material spatial realms of the desha, ooru (village) and the city that animate their lives. I study the desha as a place of familiarity created through the process of circular migration and a practice of inhabitation deployed to mitigate the uncertainty of this form of internal migration. By studying the ooru and the city through the frameworks of belonging and estrangement, I explore how these spaces work as affective and material resources for migrants despite their ambivalence towards them. Through these explorations, this article argues for a refiguration of the concept of circular migration as an interpretive device such that it can better capture the fluidities of contemporary mobilities.